Risk Factors for Single and Multiple Recurrences for Endoscopic Retrograde Cholangiopancreatography and Open Choledochotomy in Treating Choledocholithiasis - Yao Wu; Ying Zhang; Xiao Meng Jiang; Chen Jing Xu; Yan Yan Wang; Jin Yuan Gu; Yi Li; Shun Fu Xu (Gastroenterology Research and Practice)
Background. There are few studies comparing recurrences between endoscopic retrograde cholangiopancreatography (ERCP) and open choledochotomy (OCT). Aims. To compare the effect of different surgical methods on single and multiple recurrences of choledocholithiasis. Methods. A total of 1255 patients with choledocholithiasis who underwent ERCP or OCT were retrospectively studied. The recurrence of choledocholithiasis was calculated by the Kaplan–Meier method with the log-rank test. Multivariate analyses of recurrent choledocholithiasis were performed by introducing variables with P<0.20 in univariate analysis into the logistic regression model. Results. A total of 204 (16.7%, 204/1225) patients relapsed. Among the 204 patients, 74.5% relapsed within three years after surgery, of whom 39.7% (81/204) had multiple relapses (≥ 2). The recurrence rate of ERCP (17.2%, 119/692) was higher than that of OCT (15.1%, 85/563), but the difference was not statistically significant. The independent risk factors for a single recurrence of choledocholithiasis were diabetes, stone number≥2, maximum stone diameter≥15 mm, sedentary occupation, the approach of ERCP (EST or EPBD), periampullary diverticulum, primary suture, high-fat diet (postoperative), frequency of weekly vegetable intake (< 4, postoperative), and drinking (postoperative). However, the ERCP approach (EST or EPBD), OCT approach (LCBDE), primary suture, high-fat diet (postoperative), and frequency of weekly vegetable intake (< 4, postoperative) were independent risk factors for multiple recurrences of choledocholithiasis. Conclusion. Patients with choledocholithiasis should be followed up regularly for one to three years after treatment. Stone number ≥ 2, diabetes mellitus, periampullary diverticulum, surgical methods, and lifestyle are all risk factors for the recurrence of choledocholithiasis. ERCP is still the preferred surgical method based on the advantages of low risk of cholangitis recurrence, less hospital stay, minimally invasive surgery, fewer postoperative complications, and easier acceptance by elderly patients. In addition to optimizing the treatment plans, postoperative lifestyle management is also vital.